(untitled) (REMUNOM, 2025)
This study aims to analyze public educational policies in higher education and their relationship with sustainable development in Angola, highlighting current challenges and future perspectives. Education, a fundamental right enshrined in the Constitution of the Republic of Angola, must be universal and free, ensuring access for all to literacy, education, culture, and sports, while also encouraging the participation of private actors. This qualitative research adopts a bibliographic method grounded in a review of literature from institutional sources. Despite the legislation’s emphasis on the value of education, there remains a lack of effective public policies to guarantee the universalization and quality of higher education. Among the main obstacles are: an insufficient number of universities meeting appropriate standards, centralized educational management, students’ socioeconomic vulnerability, poor infrastructure, limited funding for scholarships, academic exchanges, and mobility programs, as well as the insufficient appreciation of scientific research as a tool for social, economic, technological, and cultural development. It is concluded that the implementation of consistent public policies can significantly foster the production of knowledge and innovation, thereby strengthening sustainable development. Investment in human capital, particularly through universities, represents a strategic path to achieving effective and long-lasting results.